Oriented Clay Nanotube Membrane Assembled on Microporous Polymeric Substrates - Qin, L.; Zhao, Y.; Liu, Jian; Hou, J.; Zhang, Y.; Wang, J.; Zhu, J.; Zhang, B.; Lvov, Y.; Van Der Bruggen, B. (American Chemical Society, 2016)
© 2016 American Chemical Society. Organized arrays of halloysite clay nanotubes have great potential in molecular separation, absorption, and biomedical applications. A highly oriented layer of halloysite on polyacrylonitrile porous membrane was prepared via a facile evaporation-induced method. Scanning electronic microscopy, surface attenuated total reflection Fourier transform infrared spectroscopy, and energy dispersive X-ray spectroscopy mapping indicated formation of the nanoarchitecture-controlled membrane. The well-ordered nanotube coating allowed for the excellent dye rejection (97.7% for reactive black 5) with high salt permeation (86.5% for aqueous NaCl), and thus these membranes were suitable for dye purification or concentration. These well-aligned nanotubes' composite membranes also showed very good fouling resistance against dye accumulation and bovine serum albumin adsorption as compared to the pristine polyacrylonitrile or membrane coated with disordered halloysite layer.